The Popularity of Faerlina US - World of Warcraft Classic Server: Game Study Using Qualitative Research Methods on the World of Warcraft Classic Game Server - Deddy Stevano H. Tobing (MEDIASI : Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2020)
This research discusses the popularity of Faerlina US which is one of the game server of the game World of Warcraft Classic (WoW Classic), a MMORPG (Massively Multiplayer Online Role Playing Game) game version which is one of the World of Warcraft game version released on 26 August 2019. This study uses several qualitative research methods, namely participatory observation, in-depth interviews, and studies of previous studies. The results of this study indicate that the popularity of Faerlina US tends to be driven by the popularity of twitch.tv streamers who play on these servers. This research also shows that Faerlina has also become popular because it is interesting to be a place to conduct economic activities such as selling virtual items and conducting gold-virtual currency transactions into real money.